2003
DOI: 10.1200/jco.2003.03.129
|View full text |Cite
|
Sign up to set email alerts
|

Matched and Mismatched Allogeneic Stem-Cell Transplantation From Unrelated Donors Using Combined Graft-Versus-Host Disease Prophylaxis Including Rabbit Anti–T Lymphocyte Globulin

Abstract: A certain degree of one antigen mismatching may not compromise the outcome after UD SCT when using this rabbit ATG in addition to standard GVHD prophylaxis regimen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 25 publications
5
56
0
Order By: Relevance
“…This reflects the 5-year RFS and OS rates of 42 and 51%, respectively, for all patients. These results are consistent or even superior to those of published reports using myeloablative regimens, 15,[18][19][20] and are particularly encouraging considering that 51% of patients were not in CR at HCT, 24% patients had over 20% blasts in the BM and 27% presented blasts in the peripheral blood. Previous studies reported OS rates of 20-30% in refractory AML using standard conditioning regimens for HCT.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This reflects the 5-year RFS and OS rates of 42 and 51%, respectively, for all patients. These results are consistent or even superior to those of published reports using myeloablative regimens, 15,[18][19][20] and are particularly encouraging considering that 51% of patients were not in CR at HCT, 24% patients had over 20% blasts in the BM and 27% presented blasts in the peripheral blood. Previous studies reported OS rates of 20-30% in refractory AML using standard conditioning regimens for HCT.…”
Section: Discussionsupporting
confidence: 73%
“…12 The relatively low rate of severe acute GVHD and persistent chronic GVHD in unrelated patients might be attributable to the successful use of ATG-F, as reported by our group. 15 In particular, the successful use of ATG-F might be reflected in the lower (although not statistically significant) rate of chronic extensive GVHD after unrelated HCT compared with related HCT. It is noteworthy that, on taking into account the lower relapse risk after unrelated HCT compared with related HCT, a clinically significant negative influence on the GVL effect by ATG-F could not be observed.…”
Section: Discussionmentioning
confidence: 99%
“…5 While the efficacy of ATG to prevent GVHD and to reduce nonrelapse mortality after myeloablative HSCT has been demonstrated in several studies, the role of ATG in reduced-intensity conditioning has not been evaluated. [6][7][8][9][10] However, reduced-intensity conditioning with BU and FLU was safe even without ATG in 24 patients as shown by our group. 11 In order to assess the impact of ATG, we retrospectively compared the engraftment, incidence and severity of GVHD and survival after BU-and FLU-based reduced-intensity conditioning with or without ATG in patients who had received peripheral blood stem cell transplantation (PBSCT) from HLAidentical siblings.…”
Section: Discussionmentioning
confidence: 95%
“…8 However, the use of reinforced GVHD prophylaxis with ex vivo T-cell depletion can mitigate the impact of mismatching. 9,10 From this perspective, haplo donors present different advantages: short time to find a donor, possibility of donor-lymphocyte infusion, and/or donors are not limited in ethnic minority patients. In addition, haplo-HSCT can be a valid option for patients with a relatively large body weight, for whom an optimal cell dose from UCB is rarely found.…”
Section: Introductionmentioning
confidence: 99%